Anticorrosion Nanocrystalline Beta Zeolite Thin Film for Advanced Applications - Maha Saud M. Al-subaie; Aisha Mahmood A. Al-Turkustani; Rosilda Selvin; Saedah Rwede Al-Mhayawi (Journal of Chemistry)
Steel alloys corrosion is ubiquitous and is conventionally protected by anticorrosion chromate coatings. However, the process suffers from the release of carcinogenic hexavalent chromium ions that needs to be replaced by an ecofriendly alternative. In this context, the need for the development of satisfactory ecofriendly chromium-free coating with superior corrosion performance is highly desirable. In the present study, we synthesized fully dispersible nanocrystalline Beta zeolite seeds and coated on steel alloys followed by steaming. The samples were characterized by XRD, FE-SEM, and DLS analyses. The anticorrosion behavior of the synthesized nanoparticle coatings on steel alloys was investigated by electrochemical measurements (DC polarization) and electrochemical impedance spectroscopy (EIS) in NaCl and acid and alkaline media under identical experimental conditions. The present study demonstrated that the nanozeolite coating can be a potential alternative for toxic and carcinogenic chromate coating.